Revision of Central American species of Euryomma Stein (Diptera, Fanniidae), with description of two new species and updates of distributional records (2012)
ABSTRACT: Euryomma is the second largest genus within Fanniidae, but only two species, E. panamensis Chillcott, 1958 and E. rettenmeyeri Chillcott, 1958 have been recorded in Central America. In this paper we describe two new species of the genus found in Costa Rica, Euryomma chillcotti sp. nov. (Province of Puntarenas) and Euryomma steini sp. nov. (Provinces of Cartago and Limón). Euryomma tahami Grisales, Wolff & Carvalho, 2012 is recorded for the first time to Costa Rica. Identification key to all species found in Central America, descriptions and re-descriptions of species occurring in the region and illustrations of the terminalia of new species are presented.